2012
DOI: 10.1002/nla.1812
|View full text |Cite
|
Sign up to set email alerts
|

Krylov‐accelerated algebraic multigrid for semi‐definite and nonsymmetric systems in computational fluid dynamics

Abstract: SUMMARY This article reports on experiences with aggregation algebraic multigrid relying on Krylov acceleration on each level of the grid hierarchy as preconditioners for linear systems in general purpose fluid flow simulation software. In benchmarks that reflect the requirements of industrial simulations, it is demonstrated that for semi‐definite problems, the performance of recently published algorithms of this type is very attractive but that proposed variants of these algorithms occasionally fail for nonsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Moreover, our solver must be robust enough for meshes with a quality typical for industrial applications. We prefer therefore to construct our own solver based on the experience we had with both, segregated (elliptic) problems, see Emans [6,8], and coupled problems of another kind, see Emans [11,13].…”
Section: Numerical Solution Of the Linear Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, our solver must be robust enough for meshes with a quality typical for industrial applications. We prefer therefore to construct our own solver based on the experience we had with both, segregated (elliptic) problems, see Emans [6,8], and coupled problems of another kind, see Emans [11,13].…”
Section: Numerical Solution Of the Linear Systemsmentioning
confidence: 99%
“…Further aspects of the AMG algorithm. Our experience with the velocitypressure coupling has shown that the robustness of GMRES-based k-cycle AMG, see Emans [13], is indispensable in the first iteration of this scheme. Later on, if the current solution is no longer far away from the physical solution, the systems become easier to solve.…”
Section: Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…In , Emams reports on experiences with aggregation AMG relying on Krylov acceleration as preconditioners for linear systems in general purpose fluid flow simulation. In benchmarks that reflect the requirements for industrial situations, the performance of recently published algorithms for semi‐definite problems is shown to be very attractive except for proposed variants that occasionally fail for nonsymmetric problems; modifications are suggested to lead to reliable solvers for these situations.…”
mentioning
confidence: 99%